2015
DOI: 10.12693/aphyspola.127.1732
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Corneal Neovascularisation with the Use of Image Processing Techniques

Abstract: The aim of the article is to present the developed technique to measure the degree of neovascularisation of the cornea image in visible light. The study used an image sensor attached to a slit lamp. The proposed technique consists in performing segmentation of the color image to enhance blood vessels and setting values of the degree of cornea neovascularisation. Comparison of the indicator before and after treatment of the cornea can objectively assess the eectiveness of the adopted method of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The camera has a lens with a focal length of 16mm, visible light filter, infrared radiator and radiator driver. The operation of the controller and IR radiator is discussed in [15][16]. The experiment was performed in the configuration shown in [1][2].…”
Section: Study Of Distance Range Visual Measurement In the Newmentioning
confidence: 99%
“…The camera has a lens with a focal length of 16mm, visible light filter, infrared radiator and radiator driver. The operation of the controller and IR radiator is discussed in [15][16]. The experiment was performed in the configuration shown in [1][2].…”
Section: Study Of Distance Range Visual Measurement In the Newmentioning
confidence: 99%
“…The camera was equipped with a tripod, a lens with a brightness of F = 2.0 with a fixed focus of f = 16 mm, visible light filter (high-pass filter, λ ≥ 850nm), infrared illuminator with the wavelength λ = 850 nm and a illuminator driver. The operation of the controller and the IR lamp together are discussed in [19] - [21]. The experiment was performed in the configuration shown in Fig.…”
Section: Measurement System Configurationmentioning
confidence: 99%
“…The measurement was done using the technique described in [16]. The study was carried out in a setup as shown in Fig.…”
Section: Measurement System Congurationmentioning
confidence: 99%
“…The multiple measurements were repeated to reduce the impact of random errors resulting from the use of a highly sensitive (of 0.01 mm accuracy) dial gauge. The signal resulting from the vibration of the membrane was obtained using the technique presented in [16]. This technique requires the use of a marker.…”
Section: Description Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation